2017
DOI: 10.1097/qad.0000000000001353
|View full text |Cite
|
Sign up to set email alerts
|

Improved kidney function in patients who switch their protease inhibitor from atazanavir or lopinavir to darunavir

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Interestingly, in our study, we found lower baseline eGFR, nadir CD4 counts, uncontrolled viremia, and current PI/r use associated with incident CKD. Although we did not have adequate power to determine which PI/r was associated with CKD, previous analyses have indicated that ATV causes nephrolithiasis and is associated with development of interstitial nephritis, switching from ATV/r or LPV/r to DRV/r is associated with improvement in kidney function, and use of a concomitant PI/r with TDF amplifies the renal toxicity of the later due to inhibition of Multi‐resistant Protein 4 (MRP‐4) efflux channels in the proximal tubular cells by ritonavir leading to TDF accumulation in the cells …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in our study, we found lower baseline eGFR, nadir CD4 counts, uncontrolled viremia, and current PI/r use associated with incident CKD. Although we did not have adequate power to determine which PI/r was associated with CKD, previous analyses have indicated that ATV causes nephrolithiasis and is associated with development of interstitial nephritis, switching from ATV/r or LPV/r to DRV/r is associated with improvement in kidney function, and use of a concomitant PI/r with TDF amplifies the renal toxicity of the later due to inhibition of Multi‐resistant Protein 4 (MRP‐4) efflux channels in the proximal tubular cells by ritonavir leading to TDF accumulation in the cells …”
Section: Discussionmentioning
confidence: 99%
“…The chronic kidney disease-epidemiology formulation was used to convert creatinine measurements to eGFR [14], and serial eGFR measurements were used to generate eGFR slopes which capture the direction and rate of change of eGFR and as such provide an indicator of changing renal function over time [15]. Follow-up was stratified by time exposed to TDF (from first to last exposure irrespective of interruptions), time exposed to TAF (censored at TAF discontinuation or last visit on TAF), and time on no ART or non-tenofovir-containing ART (excluded from the analyses).…”
Section: Methodsmentioning
confidence: 99%
“…The models were fully adjusted for the following factors: age at switch, gender, ethnicity, eGFR at TDF/ TAF initiation, and time-updated CD4 cell count, HIV RNA [undetectable (< 50 HIV-1 RNA copies/mL) or detectable] and cumulative TDF use (where relevant). Subgroup analyses were performed that restricted analyses to those with rapid eGFR decline (we considered two definitions: decline in eGFR of > 3 or 5 mL/min/1.73 m 2 / year [15] as estimated from unadjusted eGFR slopes in the mixed effects model) or CKD (defined as eGFR < 60 mL/min/1.73 m 2 ) while receiving TDF. All analyses were performed using STATA 15 (StataCorp LLC, College Station, TX).…”
Section: Methodsmentioning
confidence: 99%
“…[85][86][87][88][89] Observational cohort studies have also linked atazanavir and lopinavir/ritonavir to rapid eGFR decline and incident CKD, 78,79 and switching from ritonavir-boosted atazanavir or lopinavir to boosted darunavir has been associated with improved kidney function. 90 In settings where TAF, abacavir, and darunavir are available, the use of TDF, atazanavir, and lopinavir/ritonavir should ideally be avoided in those with CKD, rapid eGFR decline (>3-5 ml/min per 1.73 m 2 per year), or at high CKD risk. The threshold for avoiding or discontinuing these agents may be influenced by local circumstances.…”
Section: K D I G O E X E C U T I V E C O N C L U S I O N Smentioning
confidence: 99%